Explaining the interplay between merchant acceptance and consumer adoption in two-sided markets for payment methods - Kim P. Huynh; Gradon Nicholls; Oleksandr Shcherbakov (Bank of Canada, 2019)
The market for payment cards is inherently two sided. Consumers benefit from increased merchant acceptance of payment cards and vice versa. To quantify the interdependence of consumer and merchants or network externalities, we construct and estimate a structural two-sided model of a payment choice. We exploit a unique dataset consisting of the Bank of Canada's consumer methods-of-payment survey diaries and the Retailer Survey on the Cost of Payment Methods. We find that consumer adoption of payment cards is inelastic. When merchants face an increase in the usage cost of credit cards, they reduce their acceptance of credit cards in favor of debit cards, and there is a small increase in the share of cash-only businesses. If the usage cost of cash for both sides of the market increased by an order of magnitude, cash would still be used at the point of sale. We also show that under full adoption and acceptance of all payment instruments by both sides of the market, consumers and merchants would continue using cash for approximately one out of five transactions.
Keywords: L13; L15; L81; L96; C51; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods; Financial services